Clinical feasibility of imaging with indocyanine green combined with carbon nanoparticles for sentinel lymph node identification in papillary thyroid microcarcinoma. Issue 36 (September 2019) - Zhang, Xing; Shen, Yan-Ping; Li, Jia-Gen; Chen, Gun
Abstract: Background: Although several previous studies demonstrated the feasibility and efficacy of indocyanine green (ICG) for thyroid cancer surgery, ICG was administered through venous injection and focused on parathyroid gland protection. We thus aimed to study the feasibility of imaging using ICG combined with carbon nanoparticles (CNs) in the identification of sentinel lymph nodes (SLNs) in patients diagnosed with papillary thyroid microcarcinoma (PTMC). Methods: Two approaches were applied to detect lymph nodes in PTMC surgery. Patients were randomized into 2 groups. ICG and CNs were injected into the thyroid in Group A. In Group B, only CNs was injected. Black-stained or fluorescent nodes observed using near-infrared fluorescence imaging systems were defined as SLNs. SLN and central lymph node (CLN) dissection was completed in both groups. The pathological and postoperative outcomes were compared between 2 groups. Results: There were 40 patients in Group A and 60 in Group B. A total of 138 SLNs were identified; 72 and 66 SLNs were detected and dissected in Groups A and B, respectively. The number of SLNs identified (per patient) in Group A was higher than that in Group B ( P = .027). The number of harvested CLNs was 161 and 192 in Groups A and B, respectively, out of which 45 and 48 lymph nodes with metastasis were confirmed by permanent pathology. The CLN metastatic rate in Group A was higher than that in Group B ( P = .048). Conclusion: Imaging using ICG combined CNs is feasible and safe for SLN identification in PTMC patients. Compared with using only CNs, more SLNs can be removed and more metastatic lymph nodes can be confirmed when using the combined method. Although the combined method appears to accurately stage tumors, further research is needed.